Pediatric Absence Status Epilepticus: Prolonged Altered Mental Status in an 8-Year-Old Boy - Adams, Scott J. (Case Rep Neurol Med, 2016)
Absence status epilepticus is characterized by a prolonged state of impaired consciousness or altered sensorium with generalized electroencephalographic abnormalities. It is most commonly diagnosed in patients with known idiopathic generalized epilepsy; however, it may also be the first presentation of epilepsy. Due to the subtle and variable manifestations of the condition, absence status epilepticus may be underrecognized, particularly in children. We present the case of an 8-year-old boy who experienced two episodes of prolonged altered mental status, subsequently determined to be absence status epilepticus with idiopathic generalized epilepsy with phantom absences. We discuss the classification, pathophysiology, clinical presentation, and electroencephalographic findings of pediatric absence status epilepticus and provide a practical overview for management.